Rapid post-glacial bedrock weathering in coastal Norway - Andersen, Jane Lund; Margreth, Annina; Fredin, Ola; Linge, Henriette; Goodfellow, Bradley W.; Faust, Johan C.; Knies, Jochen; Solbakk, Terje; Brook, Edward J.; Scheiber, Thomas; Van der Lelij, Roelant; Burki, Valentin; et al. (Elsevier, 2022)
Quantifying bedrock weathering rates under diverse climate conditions is essential to understanding timescales of landscape evolution. Yet, weathering rates are often difficult to constrain, and associating a weathered landform to a specific formative environment can be complicated by overprinting of successive processes and temporally varying climate. In this study, we investigate three sites between 59 degrees N and 69 degrees N along the Norwegian coast that display grussic saprolite, tafoni, and linear weathering grooves on diverse lithologies. These weathering phenomena have been invoked as examples of geomorphic archives predating Quaternary glaciations and consequently as indicators of minimal glacial erosion. Here we apply cosmogenic nuclide chronometry to assess the recent erosional history. Our results demonstrate that all three sites experienced sufficient erosion to remove most cosmogenic nuclides formed prior to the Last Glacial Maximum. This finding is inconsistent with preservation of surficial (<1-2 m) weathered landforms under non-erosive ice during the last glacial period, while simultaneously demonstrating that post-glacial weathering and erosion rates can be locally rapid (4-10 cm kyr(-1)) in cold temperate to subarctic coastal locations. (C) 2021 The Authors. Published by Elsevier B.V. ISSN:0169-555x ISSN:1872-695X